Faktor-Faktor yang Mempengaruhi Environmentally Conscious Consumer Behavior: Peran Mediasi Perceived Consumer Effectiveness - Anggraeni, Dwi; Balqiah, Tengku Ezni (UI Scholars Hub, 2021)
Consumer interest in environmental issues attracts researchers to understand the factors that in- fluence consumer behavior in an environmentally friendly manner. This study aims to show the ef- fect of enviromental knowledge, religiosity, and perceived consumer effectiveness on environmentally conscious consumer behavior. Purposive sampling was used to collect 261 millennial respondents through a survey. There were 10 research hypotheses tested using the Structural Equation Model- ing technique through Lisrel 8.8 software. The results of data processing show the direct influence of environmental knowledge and religiosity on environmentally conscious consumer behavior also through mediation of perceived consumer effectiveness. This study enriches the existing literature on environmentally conscious consumer behavior in Indonesia and contributes to Indonesian companies in designing their green marketing strategies to be more effective in creating millennial generation in Indonesia.